2010
DOI: 10.1210/me.2010-0192
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Regulates Metabolic Actions of Glucocorticoids by Phosphorylating the Glucocorticoid Receptor through p38 MAPK

Abstract: Glucocorticoids play central roles in the regulation of energy metabolism by shifting it toward catabolism, whereas AMP-activated protein kinase (AMPK) is the master regulator of energy homeostasis, sensing energy depletion and stimulating pathways of increasing fuel uptake and saving on peripheral supplies. We showed here that AMPK regulates glucocorticoid actions on carbohydrate metabolism by targeting the glucocorticoid receptor (GR) and modifying transcription of glucocorticoid-responsive genes in a tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 64 publications
2
57
0
10
Order By: Relevance
“…Our observation that p38 MAPK regulates GR phosphorylation at S203 combined with the fact that in other cell types p38 MAPK also phosphorylates GR at S211 (13,46) suggests that this kinase can affect GR function by acting on multiple serine residues. In line with this, we showed that p38 MAPK can suppress GR function by exerting two opposite actions on GR key serine residues, namely directly phosphorylating S203 and interfering with GR phosphorylation at S211.…”
Section: Discussionmentioning
confidence: 81%
“…Our observation that p38 MAPK regulates GR phosphorylation at S203 combined with the fact that in other cell types p38 MAPK also phosphorylates GR at S211 (13,46) suggests that this kinase can affect GR function by acting on multiple serine residues. In line with this, we showed that p38 MAPK can suppress GR function by exerting two opposite actions on GR key serine residues, namely directly phosphorylating S203 and interfering with GR phosphorylation at S211.…”
Section: Discussionmentioning
confidence: 81%
“…Smad6 suppresses GR-induced transactivation by attracting HDAC3 to DNA-bound GR and by antagonizing acetylation of histone H3 and H4 induced by p160/SRC1 [64]. In addition, AMP-activated kinase (AMPK) counteracts GC/GR-induced upregulation of the gluconeogenic program in liver by specifically phosphorylating the GR at serine 211 and releasing p300 and the SWF/SNF chromatin remodelling complex component SNF2 from gluconeogenic GR target gene promoters [65], suggesting that AMPK may directly link cellular energy status to systemic Bereitgestellt von | Uppsala University Library Angemeldet Heruntergeladen am | 17.11.14 12:00 glucose homeostasis through the control of GR-associated transcriptional co-factor complexes in the liver.…”
Section: Gcs In Glucose Homeostasismentioning
confidence: 99%
“…SMAD6 suppresses GR-mediated transactivation by attracting histone deacetylase 3 (HDAC3) to DNAbound GR and subsequently, antagonizing acetylation of histone H3 and H4 induced by SRC-1 (63). In another unique mechanism, Nadar et al (2010) recently found that phosphorylation of GR at serine 232 by MAPK p38 can discharge p300 and the SWF/SNF chromatin remodelling complex component SNF2 from gluconeogenic GR bound promoters in rat liver (64). Since AMP-activated kinase (AMPK) activates MAPK p38, this provides a mechanism by which the organism 'senses' its low energy status and turns-off ATP-consuming metabolic programs including gluconeogenesis (65).…”
Section: Role Of Gcs In the Regulation Of Hepatic Gluconeogenesismentioning
confidence: 99%
“…Since AMP-activated kinase (AMPK) activates MAPK p38, this provides a mechanism by which the organism 'senses' its low energy status and turns-off ATP-consuming metabolic programs including gluconeogenesis (65). Indeed, when rats were treated with the AMPK activator AICAR, Dex-induced hepatic steatosis and gluconeogenesis were attenuated (64).…”
Section: Role Of Gcs In the Regulation Of Hepatic Gluconeogenesismentioning
confidence: 99%